Solid wetting-layers in inorganic nano-reactors: the water in imogolite nanotube case. Issue 5 (24th April 2020) - Monet, Geoffrey; Paineau, Erwan; Chai, Ziwei; Amara, Mohamed S.; Orecchini, Andrea; Jimenéz-Ruiz, Mónica; Ruiz-Caridad, Alicia; Fine, Lucas; Rouzière, Stéphan; Liu, Li-Min; Teobaldi, Gilberto; Rols, Stéphane; et al.
Abstract : The discovery of an original structure of the water at the inner surface of inorganic aluminogermanate nanotubes and its specific dynamics are reported, based on density functional theory molecular dynamics and inelastic neutron scattering. Abstract : By combined use of wide-angle X-ray scattering, thermo-gravimetric analysis, inelastic neutron scattering, density functional theory and density functional theory molecular dynamics simulations, we investigate the structure, dynamics and stability of the water wetting-layer in single-walled aluminogermanate imogolite nanotubes (SW Ge-INTs): an archetypal system for synthetically controllable and monodisperse nano-reactors. We demonstrate that the water wetting-layer is strongly bound and solid-like up to 300 K under atmospheric pressure, with dynamics markedly different from that of bulk water. Atomic-scale characterisation of the wetting-layer reveals organisation of the H2 O molecules in a curved triangular sublattice stabilised by the formation of three H-bonds to the nanotube's inner surface, with covalent interactions sufficiently strong to promote energetically favourable decoupling of the H2 O molecules in the adlayer. The evidenced changes in the local composition, structure, electrostatics and dynamics of the Ge-INT's inner surface upon the formation of the solid wetting-layer demonstrate solvent-mediated functionalisation of the nanotube's cavity at room temperature and pressure, suggesting new strategies for the design of nano-rectors towards potential control of chemical reactivity in nano-confined volumes.